"The American-Russian Conflict Over Natural Resources in the Caspian Sea Region." (Tikrit Journal For Political Science, 2023)
The Caspian Sea region has great importance because of the natural resources it contains, which was a driver of the nature of international interactions, especially between the United States of America and the Russian Federation. Washington wanted to control the energy resources in the region, weaken Russian influence there, encircle Iran, and prevent it from infiltrating the Caspian Sea countries. The United States expanded The American government sought to create a new situation, represented by the removal of energy transmission lines in the region from Russian hegemony. The Azerbaijani-American rapprochement to invest in oil resources affected the expansion of the base of the conflict. This unilateral decision was made without consulting its main partners, Russia and Iran. It also led a campaign to restore Dividing the wealth of the Caspian Sea between the five countries, at a time when Iran rejects this approach from Azerbaijan, saying that it did not choose a suitable partner well, and that this will open the doors of the region to Western influence, which affects the strategy of both Russia and Iran in the region.
Keywords: conflict, American, Russian, energy sources, Caspian Sea